The chemical composition of the secretions, their antibacterial activity, and the pygidial gland morphology of selected European Carabini ground beetles (Coleoptera: Carabidae) - Vesović, Nikola; Nenadić, Marija; Vranić, Sofija; Vujisić, Ljubodrag; Milinčić, Katarina M.; Todosijević, Marina; Dimkić, Ivica; Janakiev, Tamara; Ćurčić, Nina B.; Stevanović, Nataša; Mihajlović, Ljiljana; Vukoičić, Danijela Ž.; et al. (Frontiers in Ecology and Evolution, 2023)
Pygidial glands are known to produce strong-smelling vapours in carabids. We explored the chemical composition of the pygidial gland secretions, and the morphology of the glands in five Carabini ground beetle species (one species from the subtribe Calosomatina and four species from the subtribe Carabina): Calosoma (Calosoma) maderae (Fabricius, 1775), Carabus (Carabus) granulatus Linnaeus, 1758, Carabus (Limnocarabus) clathratus Linnaeus, 1760, Carabus (Carabus) ulrichii Germar, 1823, and Carabus (Procerus) gigas Creutzer, 1799. Additionally, we tested the antibacterial potential of the pygidial gland secretions of the two latter species. In order to detect the chemical content of the secretions, we used gas chromatography-mass spectrometry (GC-MS). The secretion extracts were applied against selected strains of medically important bacteria. We used bright-field microscopy to examine the morphology of the glands. In total we found 11 chemical compounds in the pygidial gland extracts of the analysed ground beetles. Ten chemicals were identified (seven carboxylic acids, two hydrocarbons, and one aromatic aldehyde), while one chemical remained unidentified. Most of the components were isolated from the secretion of C. (L.) clathratus (nine), while the lowest number of compounds was found in C. (P.) gigas (two). Methacrylic acid was the most dominant compound by percentage in all five species, while angelic acid was also detected in all samples. As expected, salicylaldehyde was exclusively found in the species of the genus Calosoma Weber, 1801. We tested the antibacterial potential of the pygidial gland secretions of two Carabus Linnaeus, 1758 species against 11 bacterial strains. The secretion of C. (P.) gigas was shown to achieve the highest level of antibacterial activity against Pseudomonas aeruginosa, Salmonella enterica, and S. typhimurium (even the same level as the positive control streptomycin), while the secretion of C. (C.) ulrichii achieved the highest antimicrobial potential against Staphylococcus epidermidis, S. aureus, Listeria monocytogenes, and Bacillus cereus. The most noticeable difference in the morphology of the glands of the two genera is the more drastic narrowing of the reservoir in the transition to the efferent duct in Calosoma compared to Carabus.